Global security watch : China - Weitz, Richard (Global security watch series., 2013)
Global Security Watchâ€"China presents a comprehensive overview of the main foreign and defense policies of the People's Republic of China, emphasizing the political-military developments in the modern era since the 1989 Tiananmen Square incident. It prov